Educação ambiental em unidade de conservação: o caso do parque natural municipal de Pouso Alegre, Minas Gerais. - Simões, Noéle Aparecida (2023)
The human being has been establishing relationships with the environment of which he is a part and making use of the resources available in nature to meet his needs, however, the excessive and unbridled exploitation that has been accentuated in contemporary societies has triggered a series of consequences, boosting environmental movements and putting on the agenda important issues such as the development of environmental education (EA) and the maintenance of protected areas. In this context, the main objective of this research was to analyze the contribution of perception and environmental education to the conservation of the Municipal Natural Park of Pouso Alegre (PNMPA), as well as to explain possibilities and limitations for its implementation, through the investigation of the projects carried out in the conservation unit (UC) and analyzes of the environmental perceptions of public school students in the municipality and employees of the Natural Park. The methodology had two stages, the first of which involved a bibliographical and documental research phase. And, in the second, there was a case study with field visits in loco to carry out interviews and the application of questionnaires with visiting students and with the technical team of the UC. Data were collected between the months of September and December 2022. The analysis of the testimonies occurred through the adaptation of the Content Analysis Method and were contrasted with the theoretical framework. The results reveal that different EA projects and activities occur for the Natural Park public, however, there are still challenges for its effective implementation and management difficulties, arising from current and recurring environmental problems in the place. It turned out that the naturalist and conservationist conceptions of the environment are still very present, both in the view of visiting students and technical managers. And that the predominant EA macrotrend in the UC is the conservationist one. This implies the importance of new practices and actions based also on a more critical and participatory environmental education, aiming to broaden the socio-environmental vision, which is essential for achieving a sustainable society. Therefore, it is desirable that more partnerships occur with the formal educational spaces of the municipality and region, seeking to give visibility to the Natural Park, attract greater public interest and show the population its real role as a protected area that provides relevant environmental and ecosystem services.